Heat Transfer Analysis in Reiner–Philippoff Fluid via Finite Element Approach - Jabbar, N.; Sumelka, W.; Nazir, U. (Acta Physica Polonica A, 2024)
In this article, we discuss the increase in Reiner–Philippoff liquid thermal energy and mass transfer through a perpendicular plane in the presence of the magnetizing field. Characterizations regarding mass dissipation and heat energy are improved using non-Fourier's analysis with the existence of a thermal source. Three kinds of nanoparticles, i.e., titanium dioxide, silicon dioxide, and aluminum oxide, are introduced in engine lubricants to create thermal energy. Darcy–Forchheimer analysis is adopted to examine the effects of flow and thermal energy. Furthermore, the Dufour and Soret effects are also discussed. A developing model is converted into a system of ordinary differential equations using similarity variables and solved using the finite element method. It is observed that the heat energy of the fluid increased as opposed to a higher rate of time relaxation number. Moreover, the fluid concentration declined as opposed to changes in the Schmidt number and chemical reaction parameters.